SKALA EVALUASI LINGKUNGAN BELAJAR KLINIK, SUPERVISI DAN DOSEN PERAWAT (CLINICAL LEARNING ENVIRONMENT, SUPERVISION AND NURSE TEACHER – CLES+T) VERSI BAHASA INDONESIA: VALIDITAS DAN RELIABILITAS - Ratna Puji Priyanti; Pepin Nahariani (Universitas Nahdlatul Ulama Surabaya, 2016)
The practice of clinical learning is a bridge for gap between theory and practice. By learning practice clinics, nursing students are encouraged to prepare for graduate and worked in clinical practice. Evaluation of clinical learning environment needed to be able to create a conducive learning environment. CLES+T scale has been validated and used in more than 30 countries.The research aims is to validate the CLES+T scale into Indonesian version. CLES + T has been translated into Indonesian version using the rules of the international translation backward and forward. Construct validity using 4 oang experts in nursing and education. The SCVI result was 0.9405. Validity analysis was tested using PCA (Principal Component Analysis) with N = 46. Reliability tested using Cronbach's alpha. The results obtained eigenvalue and explanation precentage of 67%, it is concluded that the eigenvalue factors of CLES+T were sufficient. Cronbach alpha was obtained for 0786. CLES+T Indonesian version has been validated and can be used to evaluate learning environment as perceived by nursing students in Indonesia.